New Addition of Twenty Lichen Species to the Flora of Odisha: A Report - Mishra, Ramakanta; Chand, Pradeep Kumar; Satapathy, Kunja Bihari (Asian Journal of Biological and Life Sciences)
Panchadhara Hill range is one of the distinguished forest ranges of Odisha highly enriched with a large number of angiospermic flora. The present paper reports the occurrence of 20 species of crustose lichens for the first time in the state of Odisha while exploring the lichen diversity of the area. A morpho-taxonomic note together with habitat and distribution of all the newly reported lichen species is provided. The newly recorded lichen taxa belong to 14 genera such as Amandinea, Arthothelium, Arthopyrenia, Baculifera, Buellia, Cococarpia, Collema, Cratiria, Cryptothecia, Dimelaena, Fissurina, Graphis, Herpothallon and Pyxine and 6 families including Arthoniaceae, Arthopyreniaceae, Caliciaceae, Coccocarpiaceae, Collemataceae, and Graphidaceae. The specimens were collected from different substrata such as bark and twigs from the forests of the hill range and the identification of lichen species was done by critically studying their morphology, anatomy and chemistry. The newly reported lichen taxa included Amandinea punctata (Hoffm.) Coppins and Scheid., Arthopyrenia grisea (Schleich. ex Schaer.) Korber, Arthopyrenia minor R.C. Harris, Arthothelium abnorme (Ach.) Muell. Arg., Baculifera cutisii (Tuck.) Marb., Buellia aethalea (Ach.) Th., Buellia disciformis (Fr.) Mudd., Cococarpia erythroxyli (Spreng.) Swinscow and Krog, Collema nigrescens Degel, Collema pulcellum var. subnigrescens (Muell. Arg.) Degel., Collema subflaccidum Degel, Cratiria obscurior (Stirt.) Marbach and Kalb, Cryptothecia striata G. Thor, Dimelaena tenius (Muell. Arg.) H. Mayrhofer and Wippel, Graphis lineola Ach., Fissurina comparimuralis Staig., Graphis pseudoserpens Chaves, Lucking and Umana, Herpothallon granulare (Sipman) Aptroot and Lücking, Pyxine petricola Nyl. and Pyxine sorediata (Ach.) Mont. which were found to be an addition to lichen flora of Odisha. It is evident from the present study that Panchadhara Hill Range has a rich diversity of lichen flora. Since many of these lichen species are likely to be endemic to the special habitats of this region, they are most vulnerable to extinction and it is extremely important to document the existing lichen vegetation and to study the effect of biotic pressures on it.
Keywords: Flora; Lichens; New records; Odisha; Panchadhara